Influence of estrous cycle hormonal fluctuations and gonadal hormones on the ventilatory response to hypoxia in female rats - Marques, Danuzia A. [UNESP]; de Carvalho, Débora; da Silva, Glauber S. F. [UNESP]; Szawka, Raphael E.; Anselmo-Franci, Janete A.; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Springer Nature, 2017)
Sex hormones may influence many physiological processes. Recently, we demonstrated that hormonal fluctuations of cycling female rats do not affect respiratory parameters during hypercapnia. However, it is still unclear whether sex hormones and hormonal fluctuations that occur during the estrous cycle can affect breathing during a hypoxic challenge. Our study aimed to evaluate respiratory, metabolic, and thermal responses to hypoxia in female rats on different days of the estrous cycle (proestrus, estrus, metestrus, and diestrus) and in ovariectomized rats that received replacement with oil (OVX), estradiol (OVX + E2), or a combination of estradiol and progesterone (OVX + E2P). Ventilation (VE), tidal volume (VT), respiratory frequency (fR), oxygen consumption (VO2), and VE/VO2 were not different during the estrous cycle in normoxia or hypoxia. Body temperature (Tb) was higher during estrus, but decreased similarly in all groups during hypoxia. Compared with intact females in estrus, gonadectomized rats also had lower Tb in normoxia, but not in hypoxia. OVX rats experienced a significant drop in the ventilatory response to hypoxia, but hormonal replacement did not restore values to the levels of an intact animal. Our data demonstrate that the different phases of the estrous cycle do not alter ventilation during normoxia and hypoxia, but OVX animals display lower ventilatory responses to hypoxia compared with ovary-intact rats. Because estradiol and progesterone replacement did not cause significant differences in ventilation, our findings suggest that a yet-to-be-defined non-steroidal ovarian hormone is likely to stimulate the ventilatory responses to hypoxia in females.
Keywords: Body temperature; Breathing; Castration; Estrous cycle; Hormone replacement; Sex hormones